(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Plants are traditionally used for pharmacological activities because of its ability to produce bioactive compounds. Myristica beddomei King ssp. ustulata W.J. de Wilde is an ethnomedicinal plant and it is seen in South Western Ghats of Kerala, India. The present study assessed the phenolic content, flavonoid concentration, in vitro antioxidant and cytotoxic effect of different parts of Myristica beddomei King. The total phenolic contents in the extracts ranged from 96.29 (pericarp) to 314.47 (bark) mg g-1 gallic acid equivalent. The concentration of flavonoids in different plant part extracts ranged from 1.81 to 2.76 mg g-1 equivalent to quercetin. All the parts exhibited potential antioxidant activity with an IC50 value of 2.87 to 9.67 μg ml-1 when compared to the standard ascorbic acid with an IC50 value of 2 μg ml-1 in 1,1-diphenyl-2- picryl-hidrasil (DPPH) method. Bark showed highest activity in terms of DPPH radical scavenging (IC50 value of 2.87 µg ml-1), phosphomolybdenum test (2261.33 ± 1.65 mg g-1 trolox equivalent) and ferric ion reducing antioxidant power (FRAP) (113.1 ± 0.28 µmol Fe2+ µg-1) while pericarp showed low antioxidant activity. The in vitro screening results revealed that the seeds exhibited promising anticancer activity compared to PA1 (Ovarian Cancer) cells (50 % inhibition) were observed at a concentration 100.68 µg ml-1. In cytotoxicity test L929 (Fibroblast) cell line compared to the other parts pericarp, mace and seed needed higher concentration (>240 µg ml-1) for LC50 value. It is a promising plant for further development of antioxidant agent as it got high content of phenolic compounds and potential antioxidant and anticancer activity.